The ruling of the Federal Constitutional Court concerning the public sector purchase program: A practical way forward - Helmut Siekmann; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2020)
This paper summarizes key elements of the German Federal Constitutional Court's decision on the European Central Bank's Public Sector Asset Purchase Programme. It briefly explains how it is possible for the German Court to disagree with the ruling of the Court of Justice of the European Union. Finally, it makes suggestions concerning a practical way forward for the Governing Council of the ECB in light of these developments.
urn:nbn:de:hebis:30:3-542710
Keywords: 330